Inclusive mindedness: evolving knowledge and beliefs of preservice educators in California - McKee, Aja; Myck-Wayne, Janice; Lee, Sung Hee (Frontiers in Education, 2023)
Early childhood special educators in the United States must familiarize themselves with the importance of inclusive practices and how to successfully implement these practices to support young students with disabilities in the least restrictive environment. Depending on the credentialing program special educators in the United States complete, their understanding and training in inclusive education can vary greatly. The purpose of this study was to address the need for training in inclusion by creating an Office of Special Education Program (OSEP) grant-funded inclusive education course for preservice early childhood special educators at one university in California and then to examine how the inclusion course changed early childhood special education teacher candidates’ knowledge and beliefs of inclusion. Over 4 years, 97 early childhood special education preservice teachers participated in pre- and postcourse surveys, which determined their perceptions, understanding, and practical skills of inclusive education increased, demonstrating course effectiveness.